A systematic review on sperm DNA fragmentation in male factor infertility: Laboratory assessment - Manesh Kumar Panner Selvam (Taylor & Francis Group, 2018)
Objective: To review sperm DNA fragmentation (SDF) testing as an important sperm function test in addition to conventional semen analysis. High SDF is negatively associated with semen quality, the fertilisation process, embryo quality, and pregnancy outcome. Over recent decades, different SDF assays have been developed and reviewed extensively to assess their applicability and accuracy as advanced sperm function tests. Amongst them, the standardisation of the terminal deoxynucleotidyl transferased UTP nick-end labelling (TUNEL) assay with a bench top flow cytometer in clinical practice deserves special mention with a threshold value of 16.8% to differentiate infertile men with DNA damage from fertile men. Materials and methods: A systematic literature search was performed through the PubMed, Medline, and ScienceDirect databases using the keywords ‘sperm DNA fragmentation’ and ‘laboratory assessment’. Non-English articles were excluded and studies related to humans were only included. Results: Of the 618 identified, 87 studies (original research and reviews) and in addition eight book chapters meeting the selection criteria were included in this review. In all, 366 articles were rejected in the preliminary screening and a further 165 articles related to non-human subjects were excluded. Conclusion: There are pros and cons to all the available SDF assays. TUNEL is a reliable technique with greater accuracy and as an additional diagnostic test in Andrology laboratories along with basic semen analysis can predict fertility outcome, and thus direct the choice of an assisted reproductive technology procedure for infertile couples. Also, the TUNEL assay can be used as a prognostic test and results are beneficial in deciding personalised treatment for infertile men. Keywords: Sperm DNA fragmentation (SDF), Terminal deoxynucleotidyl transferased UTP nick-end labelling (TUNEL), DNA damage, Sperm DNA fragmentation (SDF) assay